Hotel employees and corporate social responsibility - Planinc, Tanja (Academica turistica, 2020)
Corporate social responsibility has been widely researched in recent decades across different industries. This paper attempts to explore the social aspects of corporate social responsibility in the hotel industry, focusing on the awareness of csr of employees in the selected case-study of a hotel company in Portorož, Slovenia. Specifically, their awareness of csr activities oriented towards the local community was researched. A questionnaire survey was conducted among employees, investigating their awareness of the hotel company's attitude towards the local community. Results show that it is crucial for employees to be employed in a company that participates in the development of a local community. However, they often do not know how their employer carries out activities that are related to the social aspects of corporate social responsibility.
Keywords: corporate social responsibility; družbena odgovornost; employees; hotel industry; hotelirstvo; Portorož; Slovenia; Slovenija; turizem